Friends and strangers - Sullivan, J. Courtney (Alfred A. Knopf, 2020)
"From the best-selling author of Maine, a gorgeous, compulsively-readable novel that tells the story of the complex relationship between two women, Elisabeth, a privileged new mother and writer attempting to find her footing after childbirth, and Sam, the idealistic, working-class college student she hires to nanny her young son"--